CERITA RAKYAT SENTANI: KASUARI DAN BURUNG PIPIT (Analisis Struktural Menurut Sistem Kode Roland Barthes) - Siswanto NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The folktale of Kasuari dan Burung Pipit is well-known in Sentani, Papua. As a  valuable  literature  for  Sentani people,  it  is  necessary  to  study  and  analyze  the message  of  the  folktale.  This is a qualitative research applying the descriptive method. The analysis uses a message transaction modus based on the theory of the semiotics of Roland Bhartes. The data of this research is the story of Kasuari dan Burung Pipit. The data was submitted by observation (through recordings and note-taking) and interviews. The result shows, based on the analysis, that the message transaction modus of the story includes 1)  the  proairetic  code;  2)  the heurmeuneutic code; 3) the code of semes or signifiers; 4) the symbolic code; and 5) the culture code.